Connecting lattice and molecular vibrations to organic crystal properties - Luca Catalano (IUCrJ)
Understanding dynamic processes in molecular crystals is becoming crucial for the development of next-generation smart crystalline materials. In this context, Zwolenik & Makal [(2025). IUCrJ, 12, 23–35] shed light on the complex dynamics–structure–properties relation of a pyrene derivative by correlating molecular and lattice anharmonic vibrations with the unusual thermal expansion of the compound.